Effectiveness of Mirror Therapy on Muscle Strength in Stroke Patients: A Systematic Literature Review - Saleha, Triya Yestika; Cahyati, Yanti (PT. Pubsains Nur Cendekia, 2026)
Background: Stroke is still the leading cause of death in brain health problems throughout Indonesia. In stroke patients, 70-80% of patients experience hemiparesis (muscle weakness on one side of the body). One of the rehabilitation and non-pharmacological interventions is muscle strength training, which stimulates nerves and increases functional motor/muscle strength using mirror therapy. Mirror therapy is a treatment for stroke patients that involves the mirror neuron system in the cerebral cortex and helps restore motor skills in the hands and mouth. Aims: To know the effect of mirror therapy on the muscle strength of stroke patients. Method: This research is a literature review. This review aims to review empirical evidence regarding the effectiveness of mirror therapy in improving muscle strength in stroke patients through a systematic analysis of the literature from 2019 to 2024. The PRISMA-based search and selection procedure yielded 16 articles for analysis. Results: Based on an analysis of 16 articles, mirror therapy improves muscle strength in stroke patients (p < 0.05). Conclusion: Mirror therapy can improve muscle strength and can be used as part of standard care for stroke patients with muscle weakness, both in the hospital and at home. The author recommends the application of mirror therapy in stroke patients for self-care interventions at home,